Crystal Structure of 2-Ethylimidazole-1-sulfonyl Azide: A New Azidation Reagent - Herwig Schottenberger; Sven Nerdinger; Klaus Wurst; Volker Kahlenberg; Michael Hummel; Verena Adamer; Gerhard Laus (Crystals, 2012)
Crystalline 2-ethylimidazole-1-sulfonyl azide was designed as a convenient reagent with improved thermal stability for electrophilic azidation of carbanions. The compound crystallized in the monoclinic space group P21/c. The molecules are arranged into chains by short C–H...O contacts along a two-fold screw axis. The quaternary 1-azidosulfonyl-2-ethyl-3-methylimidazolium tetrafluoroborate crystallized in Fdd2 with two independent ion pairs which engage in C–H...F interactions.